Raman spectroscopic study of the Chromobacterium violaceum pigment violacein using multiwavelength excitation and DFT calculations - Jehlička, Jan; Edwards, Howell G M; Němec, Ivan; Oren, Aharon (Spectrochimica acta. Part A, Molecular and biomolecular spectroscopy, 2015)
Violacein is a bisindole pigment occurring as a biosynthetic product of Chromobacterium violaceum and Janthinobacterium lividum. It has some structural similarities to the cyanobacterial UV-protective pigment scytonemin, which has been the subject of comprehensive spectroscopic and structural studies. A detailed experimental Raman spectroscopic study with visible and near-infrared excitation of violacein produced by C. violaceum has been undertaken and supported using theoretical DFT calculations. Raman spectra with 514 and 785 nm excitation of cultivated cells as well as extracts and Gaussian (B3LYP/6-311++G(d,p)) calculations with proposed molecular vibrational assignments are reported here.
Keywords: Chromobacterium; Cyanobacteria; Indoles; Models, Molecular; Spectrum Analysis, Raman; spektroskopie infračervená s Fourierovou transformací; indoly; Raman spectroscopy; molekulární modely; Spectroscopy, Fourier Transform Infrared; kvantová teorie; UV protective pigment; DFT calculations; Quantum Theory; Ramanova spektroskopie